2022
DOI: 10.1007/s00432-022-04317-2
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine application in cancer patients in Iran

Abstract: Purpose Nowadays, complementary and alternative medicine (CAM) is used by cancer patients all over the world. The aim of this study was to investigate the prevalence of CAM use in patients with cancer in Iran. Methods This descriptive-analytical study was conducted on 320 cancer patients in Arak. For gathering information, a researcher-made questionnaire was used. This questionnaire was consisted of two parts: demographic and clinical information; and patient’s attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Two articles did not specify it at all ( Bordbar et al, 2016 , Jalili et al, 2020 ). On the other hand, Nejat et al's study reported an average of 11.47 ± 4.02 months ( Nejat et al, 2022 ). Two studies considered the time of CAM use since diagnosis or during treatment ( Asadi Sarvestani et al, 2022 , Bazrafshani et al, 2019 ).In addition, four studies were considered this time during one year ( Farahani et al, 2019 , Dehghan et al, 2019 , Dehghan et al, 2022 , Dehghan et al, 2022 ), and two studies during six months leading to the completion of the questionnaires ( Sajadian et al, 2005 , Sajadian et al, 2009 ).…”
Section: Resultsmentioning
confidence: 97%
“…Two articles did not specify it at all ( Bordbar et al, 2016 , Jalili et al, 2020 ). On the other hand, Nejat et al's study reported an average of 11.47 ± 4.02 months ( Nejat et al, 2022 ). Two studies considered the time of CAM use since diagnosis or during treatment ( Asadi Sarvestani et al, 2022 , Bazrafshani et al, 2019 ).In addition, four studies were considered this time during one year ( Farahani et al, 2019 , Dehghan et al, 2019 , Dehghan et al, 2022 , Dehghan et al, 2022 ), and two studies during six months leading to the completion of the questionnaires ( Sajadian et al, 2005 , Sajadian et al, 2009 ).…”
Section: Resultsmentioning
confidence: 97%
“… 8 , 10 Hence, cancer survivors are recommended to undertake yoga as a regular exercise for improving their health. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%